Volume 3: Heat Transfer; Electric Power; Industrial and Cogeneration 1997
DOI: 10.1115/97-gt-010
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Surface Roughness on Heat Transfer and Aerodynamic Performance of Turbine Airfoils

Abstract: Aerodynamic flow path losses and turbine airfoil gas side heat transfer are strongly affected by the gas side surface finish. For high aero efficiencies and reduced cooling requirements, airfoil designs dictate extensive surface finishing processes to produce smooth surfaces and enhance engine performance. The achievement of these requirements incurs additional manufacturing finishing costs over less strict requirements. The present work quantifies the heat transfer (and aero) performance differences of three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…A high roughness of the blade surface leads to earlier boundary layer transition [6], increase in friction factor [7], decrease in heat transfer efficiency [8] and total pressure [9]. Boynton, et al [10] reported that smooth blades yield a turbine efficiency of 87.92%.Compared with rough blades, this was a 2.5% improvement of the efficiency, which reduced the turbine inlet temperature by 32 K and increased turbine durability.…”
Section: Introductionmentioning
confidence: 97%
“…A high roughness of the blade surface leads to earlier boundary layer transition [6], increase in friction factor [7], decrease in heat transfer efficiency [8] and total pressure [9]. Boynton, et al [10] reported that smooth blades yield a turbine efficiency of 87.92%.Compared with rough blades, this was a 2.5% improvement of the efficiency, which reduced the turbine inlet temperature by 32 K and increased turbine durability.…”
Section: Introductionmentioning
confidence: 97%
“…Kind et al [20] observed that roughness over the suction surface was more detrimental than that over the pressure surface as the velocity and adverse pressure gradient is greater over suction surface. In a rectilinear cascade [21], the aerodynamic efficiency reduces by 0.25 and 0.06 per cent for roughnesses of 2.33 and 1.03 μm, respectively, over entire blade as compared with 0.81 μm roughness. Qiang et al [22] observed that the loss coefficient increases as either exit Mach number or equivalent sand grain roughness size increases.…”
Section: Introductionmentioning
confidence: 97%
“…On the other hand, Abuaf et al [93] showed that at very low roughness levels spanning from R a = 0.8m to R a = 2.3m and flow conditions which maintained the flow near the hydraulically smooth flow regime (extrapolation of given data), virtually no heat transfer effects were seen at low Re values. At the highest Re values (2.3x10 6 ) tested, an increase in heat transfer coefficient of about 15% was seen, thus demonstrating that roughness effects in the hydraulically smooth and low transitionally rough regime are much less significant than those seen at high Re k values.…”
Section: Roughness Effects On Convective Heat Transfer In Cfr Enginementioning
confidence: 99%